Evaluating Usability And Customer Satisfaction in E-Marketplaces Using System Usability Scale and Customer Satisfaction Score - Nova Christina Sari; Yusa Putra; Alfa Hikmatun Nabilah; Revania Jeni Puspitasari (Journal of Computing and Smart Ecosystems, 2025)
In the digital era, user experience (UX) plays a critical role in determining the success of online platforms, particularly in the highly competitive e-commerce industry. This study presents a comparative evaluation of three major e-commerce applications in Indonesia namely Shopee, Tokopedia, and Lazada using two standardized instruments: the System Usability Scale (SUS) and the Customer Satisfaction Score (CSAT). A total of 100 respondents participated in the survey, which included 10 questions mapped to SUS and 10 questions mapped to CSAT. The results revealed that all three platforms scored poorly in usability and customer satisfaction metrics. Shopee achieved the highest SUS score 51, categorized as marginal, while Tokopedia 50 and Lazada 49.55. CSAT scores followed a similar pattern, with Shopee 52%, Tokopedia 55%, and Lazada 50% falling into low or very low satisfaction categories. These findings highlight the need for substantial improvements in both usability and service quality to enhance overall user experience and engagement. This study emphasizes the importance of integrating both SUS and CSAT methods to obtain a holistic understanding of user perceptions